Comparison of Polymerization Shrinkage in Methacrylate and Silorane-Based Composites Cured by different LEDs - Ayob Pahlavan; Masumeh Hasani Tabatabaei; Sakineh Arami; Mohammad Ataie; Sara Valizadeh (Tehran University of Medical Sciences, 2013)
Background and Aims: Polymerization shrinkage in Methacrylate-based composite is one of the most important factors in composite restorations failure. Silorane-based composite is introduced to compensate this drawback and claimed to have low shrinkage. The aim of this study was to evaluate the polymerization shrinkage of these two composites. Materials and Methods: In this experimental study, 5 disk shape samples for each resin composites were placed in the centre of metallic ring bonded to microscopic glass slab. Top surface of ring was covered by a glass cover slip. Glass slab and sample were placed on a special LVDT holder in order to light cure from bottom surface and to measure the polymerization shrinkage. In this study, Deflecting Disk method and LVDT (linear variable differential transducer) was used for dimensional change measurement of resin composites. In this study, two LED curing units were used for composite polymerization. Results: The mean of polymerization shrinkage in Z250 cured with LED and High Power LED was 11.15±0.08µm and 11.51±0.17µm, respectively (P=0.094), and in P90 cured with LED and High Power LED was 1.08±0.06µm and 1.16±0.12µm, respectively (P=0.019). Conclusion: Silorane-based composite (P90) showed significantly less polymerization shrinkage than that of methacrylate-based composite (Z250). For the two types of composite, there was no significant difference between the two curing units in polymerization shrinkage.